Early embryonic developmental stages of the pearl oyster Pinctada radiata (Leach, 1814) from Lattakia coast, Syria - Hassan, N.; Mansour, C.; Saker, F. (Mesopotamian Journal of Marine Sciences, 2021)
Matured brood stock of Pinctada radiata were collected from Afamia region in Lattakia coast. Three sets of spawning and larval rearing experiments were conducted during the period from July - October 2016 and the pearl oysters were successfully spawned at average temperature 31.5 ± 0.26 °C. After about 60 min, oocytes presented no germinal vesicle, rounded and measured 47.5-55 μm with an average of 50 ± 3.95 μm in diameter. Early stages of embryonic development were recorded and the polar body was observed 15 min after fertilization, trefoil stage at 1 h and 30 min, morula at 3 h and 30 min, blastula at 4 h and 50 min, gastrula at 6 h, trochophore larva at 8 h and veliger larva at 20 h. Veliger larva dimensions were 61.88 ± 3.82 μm for average length along the antero-posterior axis and 51.26 ± 5.14 μm for height along the dorso-ventral axis.